A model of mitochondrial superoxide production during ischaemia-reperfusion injury for therapeutic development and mechanistic understanding - Annabel Sorby-Adams; Tracy A. Prime; Jan Lj Miljkovic; Hiran A. Prag; Thomas Krieg; Michael P. Murphy (Redox Biology, 2024)
Ischaemia-reperfusion (IR) injury is the paradoxical consequence of the rapid restoration of blood flow to an ischaemic organ. Although reperfusion is essential for tissue survival in conditions such as myocardial infarction and stroke, the excessive production of mitochondrial reactive oxygen species (ROS) upon reperfusion initiates the oxidative damage that underlies IR injury, by causing cell death and inflammation. This ROS production is caused by an accumulation of the mitochondrial metabolite succinate during ischaemia, followed by its rapid oxidation upon reperfusion by succinate dehydrogenase (SDH), driving superoxide production at complex I by reverse electron transport. Inhibitors of SDH, such as malonate, show therapeutic potential by decreasing succinate oxidation and superoxide production upon reperfusion. To better understand the mechanism of mitochondrial ROS production upon reperfusion and to assess potential therapies, we set up an in vitro model of IR injury. For this, isolated mitochondria were incubated anoxically with succinate to mimic ischaemia and then rapidly reoxygenated to replicate reperfusion, driving a burst of ROS formation. Using this system, we assess the factors that contribute to the magnitude of mitochondrial ROS production in heart, brain, and kidney mitochondria, as well as screening for inhibitors of succinate oxidation with therapeutic potential.